2021
DOI: 10.3389/fneur.2021.745560
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Neutrophil-to-Lymphocyte Ratio in Patients With Aneurysmal Subarachnoid Hemorrhage: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: The neutrophil–to-lymphocyte ratio (NLR), as an essential systemic inflammation factor, has been widely used as a prognostic indicator in various diseases, such as malignant tumors, cardiovascular disease, and intracranial hemorrhage. An increasing number of studies have believed that NLR is a valuable predictor of prognosis for patients with aneurysmal subarachnoid hemorrhage (aSAH). However, these results remain controversial. In the current study, we planned to carry out a systematic review and meta-analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Regarding this issue, other new biomarkers have been studied, such as neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic inflammatory response index (SIRI). 57 , 58 , 59 Unfortunately, only a few studied these parameters alongside RDW, making a comparison between them difficult. One study by Huang et al compared RDW directly with NLR in aSAH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding this issue, other new biomarkers have been studied, such as neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic inflammatory response index (SIRI). 57 , 58 , 59 Unfortunately, only a few studied these parameters alongside RDW, making a comparison between them difficult. One study by Huang et al compared RDW directly with NLR in aSAH patients.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed that NLR was significantly higher in patients with ruptured IAs than those with unruptured IAs, as shown in previous studies ( 28 , 29 ). The elevated NLR at admission has been shown to predict the unfavorable functional outcome, delayed cerebral ischemia, in-hospital mortality, and rebleeding in patients with aneurysmal subarachnoid hemorrhage ( 23 , 27 , 29 31 ). An elevated NLR was also associated with aneurysm size in patients with unruptured IAs ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil-lymphocyte ratio (NLR) indicates the inflammation status in clinical practice, calculated as the absolute neutrophil count divided by the absolute lymphocyte count in the routine blood test. Elevated NLR predicts poor outcomes in patients with acute ischemic stroke, spontaneous intracerebral hemorrhage, and SAH resulting from ruptured IA ( 20 23 ). In this study, we aimed to investigate the association of NLR as a peripheral blood inflammatory marker with AWE on HR-VWI in patients with unruptured IA.…”
Section: Introductionmentioning
confidence: 99%
“…Although several previous studies had identified NLR as a biomarker for worse functional outcomes after aSAH ( 7 , 8 , 15 ), the specific relationship among them remained obscure and may be due to the following reasons. Unfavorable outcomes may be attributed to complications, such as delayed cerebral ischemia (DCI) or cerebral vasospasm (CVS).…”
Section: Discussionmentioning
confidence: 99%